Analysis of the Genetic Diversity of the European Bison (Bison bonasus) Population in Lithuania - Romualdas Lapickis; Loreta Griciuvienė; Artūras Kibiša; Indrė Lipatova; Asta Aleksandravičienė; Irma Ražanskė; Marlena Wojciechowska; Marta Kloch; Wanda Olech; Algimantas Paulauskas (Diversity, 2023)
The European bison is a species well known for its low genetic variability due to historical bottleneck incidents. Restoration of the European bison population in Lithuania began at the end of the 20th century, and the Lithuanian population was re-established with ten individuals from the Prioksko-Terrasny reserve in Russia and one free-roaming individual captured in Lithuania. This research focused on the genetic diversity and genetic structure of European bison in Lithuania based on microsatellite markers and mtDNA sequences. The results of the microsatellite analysis revealed that the Lithuanian population (n = 34) has a different genetic structure to individuals in Poland (n = 16), Germany (n = 10), and Sweden (n = 6). The analysis of the mtDNA sequences showed a low level of variation, with two haplotypes observed in the Lithuanian bison population. H1 was more frequent and was also found in Poland, Romania, and Russia. The results of this investigation show that individuals should be continuously genetically monitored, registering their migrations and relocations for the successful management of the species in Lithuania.